The killing of a Chinese bookie [videorecording (DVD)]. - Cassavetes, John, 1929-1989; Gazzara, Ben, 1930-2012; Carey, Timothy Agoglia, 1929-1994; Cassel, Seymour, 1935-2019-; Phillips, Robert, 1925-; Woodward, Morgan, 1925-2019-; Kullers, John Red (The Criterion collection, 2008)
When a gentleman's club owner runs afoul of a small-time gangster, he is forced to commit a horrible crime in a last-ditch effort to save his beloved club and way of life.